OPTIMALISASI KAPASITAS VOLUME TAMPUNGAN EMBUNG TUGU KABUPATEN KEBUMEN - Muchamad Arif Budiyanto; Indra Suharyanto (Fakultas Teknik Universitas Cokroaminoto Yogyakarta, 2022)
Kebumen District area has a tendency to rainfall which is uneven in rainfall throughout the year, namely the rainy season where there is surplus water, whereas the dry season results in deficit of water. Tugu village one if village in Kebumen, Central Java, Indonesia has a location that has the potential to be developed into a reservoir. The purpose of this study was to determine the optimal storage capacity of the reservoir. Based on the Guide to Small Pond Design Criteria for Semi-Dry Areas in Indonesia in 1997 the capacity of the reservoir is carried out by taking into account water needs, water availability and topography. After calculating, it is found that the storage capacity based on water needs (Vn) is 48,935.70 m3. Based on the analysis of water availability (potential) during the rainy season (Vh), the volume of water that can be accommodated is 7,500.00 m3. The design capacity of a reservoir (Vd), which is equal to Vd = 7,500.00 m3 with height of dam 3.00 m.